CONTEXT INPUT PROCESS PRODUCT (CIPP) EVALUATION MODEL IN THE IMPRISONER INDEPENDENCE GUIDANCE PROGRAM AS AN EFFORTS TO PREVENT RECIDIVISTS IN CLASS IIA SRAGEN PRISON - Fauzaan Mukti Dicky Marcellino; Wido Cepaka Warih (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study applies the Context, Input, Process, and Product (CIPP) evaluation model to assess the effectiveness of the independent skills development program for inmates at the Class IIA Sragen Correctional Institution as a strategy to prevent recidivism. The findings indicate that, from the context perspective, social stigma toward ex-prisoners is a major barrier to the success of the program. In terms of input, limitations in resources, including inadequately trained facilitators and insufficient training facilities, hinder program effectiveness. From the process aspect, low inmate motivation and inconsistent training schedules reduce the quality of program implementation. Meanwhile, from the product perspective, the absence of post-release support limits former inmates’ ability to apply the skills they have acquired. Overall, the study concludes that the program has not yet been fully effective in reducing recidivism. Therefore, improvements are needed, particularly in enhancing facilitator competence, providing adequate facilities, and strengthening post-release support systems. These efforts are essential to ensure that the program can better support inmates in achieving independence and successfully reintegrating into society. Keywords: CIPP Evaluation; Independent Skills Development; Recidivism